Persistence of Bleed-Air Contaminants on High-Efficiency Particulate Arrestance Filters - Omana, Michael A.; Mann, Garrett W.; Jones, Byron W.; Eckels, Steven J. (My University, 2016)
Commercial aircraft are normally pressurized and ventilated by bleed air from propulsion engine compressors. In certain situations, contaminants from an engine-related source, likely oil from leaky seals, can be introduced into bleed air supplied to the cabin—e.g. (Murawski & Supplee, 2008; Senate, 2000; Van Netten, 2005). When contamination occurs, it is very difficult to exactly identify the nature of the contamination, sometimes requiring multiple occurrences of contamination before the cause is identified or properly addressed. Of primary interest, then, is the ability to detect and determine the source of contamination following a bleed air contamination event. In a previous study, Eckels et al. proposed to determine the nature of the contamination after an event by analyzing the cabin recirculation HEPA filters present in nearly all commercial aircraft (Eckels, Jones, Mann, Mohan, & Weisel, 2014). Using gas chromatography/mass spectrometry (GC/MS), they show a statistically significant elevation in synthetic oil and certain isomers of tricresyl phosphate (TCP), an additive of jet engine oil, on recirculation filters removed from aircraft identified by the operator as potentially having air quality problems. They concluded that, while further research is necessary to validate the method, using GC/MS to analyze HEPA filter specimens from problem aircraft provides useful information as to the likely contamination source.
Citation: Omana, M. A., Mann, G. W., Jones, B. W., & Eckels, S. J. (2016). Persistence of Bleed-Air Contaminants on High-Efficiency Particulate Arrestance Filters. Journal of Aircraft, 53(5), 1574–1577. https://doi.org/10.2514/1.C033762